Effects of walnut oil on metabolic profile and transcription factors in rats fed high-carbohydrate-/-fat diets - Gencoglu, Hasan; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Juturu, Vijaya; Şahin, Kazım (Wiley, 2020)
The aim of this study was to examine the effects of walnut oil (WO) on metabolic profile and transcription factors in rats fed high carbohydrate (HCD) and high-fat diet (HFD). Forty-two male rats were divided in to six groups: (a) Control, (b) WO (20 mg/kg BW), (c) HCD (20% of sucrose), (d) HCD + WO (e) HFD (42% of calories as fat), and (f) HFD + WO. HFD and HCD intake increased final body weights by 19% and 23% and visceral fat weights by 3- and 5-fold, respectively (p < .05 for all). In addition, serum glucose, total cholesterol, triglyceride, and free fatty acids (FFA) insulin, leptin, and MDA levels increased in rats fed with HFD and HCD. WO supplementation improved these metabolic parameters (p < .05 for all). HFD + WO and HCD + WO treated groups had a significant reduction in serum and liver malondialdehyde (MDA) levels by 12% or 15% (p < .05 for both). In addition, WO supplementation lowered the levels of hepatic nuclear factor kappa B (NF-kappa B) and NADPH oxidase subunit p22(phox), whereas increased the endothelial-NO synthase (e-NOS), nuclear factor erythroid 2-related factor-2, and sirtuin-1 levels. In conclusion, WO supplementation could alleviate the adverse impacts of both HCD and HFD in the rats. Practical applications This study suggests that WO intake can modulate carbohydrate metabolism and increase antioxidant capacity. These properties might be partially mediated through the regulation of the transcription factors and some proteins involved in energy metabolism, as well as a balance of oxidative stress, and insulin sensitivity.
Keywords: antioxidant; high carbohydrate; high-fat diet; oxidative stress; walnut oil